Endoplasmic Reticulum Export Site Formation and Function in Dendrites - Aridor, Meir (J Neurosci, 2004)
The elongated and polarized characteristics of neurons render targeting of receptors to the plasma membrane of distal axonal projections and dendritic branches a major sorting task. Although the majority of biosynthetic cargo synthesis, transport, and sorting are believed to occur in the soma, local membrane protein translation and sorting has been reported recently to take place in dendrites and axons. We investigated where endoplasmic reticulum (ER) export occurs in dendrites using an in vitro permeabilized neuron system that enables us to specifically control the assembly of ER export sites. We show that ER export sites are assembled regularly throughout the entire dendritic tree by the regulated sequential recruitment of Sar1 and COPII (coat protein complex II). Moreover, activation of metabotropic glutamate receptors leads to the recruitment of the NMDA receptor subunit NR1 to remodeled ER export sites. We propose that regulation of receptor assembly and export from the ER in dendrites plays an important role in modulating receptor surface expression and neuronal function.